Criminal Sanctions Against Perpetrators of Sirri Marriage Article 143 of the Draft Law on Material Law of Religious Courts in the Field of Marriage in the Concept of Maslahat of Sheikh Ramadhon Al-Buthy - Naachy, Dzin Nun (Sekolah Tinggi Agama Islam At-Tahdzib Jombang, 2024)
This study analyzes the criminal sanctions for sirri marriages (unregistered marriages) as regulated in Article 143 of the Draft Bill on Substantive Law for Religious Courts using Syekh Ramadhan al-Buthy’s concept of maslahat. Employing a juridical-philosophical method, this research examines legal regulations normatively and links them to Islamic values in maqashid syariah. The findings reveal that criminal sanctions for sirri marriages aim to maintain social order through marriage registration, which aligns with the protection of lineage and property. Analysis based on al-Buthy’s five criteria of maslahat demonstrates that the sanctions fall within the scope of maqashid syariah, without conflicting with the Qur’an, sunnah, qiyas, or higher maslahat. However, implementing these sanctions faces social resistance due to adherence to classical fiqh views. Educational approaches and administrative incentives are necessary to encourage marriage registration as a legal safeguard. In conclusion, the criminal sanctions against sirri marriages under Article 143 of Rancangan Undang-Undang Hukum Materil Peradilan Agama Bidang Perkawinan align with maslahat principles and can provide societal benefits if implemented wisely.